Research trends in 'trans-' studies on writing: A bibliometric analysis. (December 2021) - Sun, Yachao; Lan, Ge
Abstract: This study identifies the research trends of ' trans -' studies on writing by analyzing 165 journal articles from a bibliometric approach. The corpus consists of peer-reviewed journal articles published from 2011 to 2020, during which ' trans -' studies on writing experienced rapid development in its conceptualization and implementation. Our analysis concentrates on (1) the most highly cited authors and articles and (2) the most frequently discussed concepts and their changes over the past decade. The results reveal that translingual practice, a concept that is mainly developed by Suresh Canagarajah (2013a, 2013b, 2015, 2018), has been increasingly adopted to illustrate language practices in writing processes. Other concepts, such as translingual approach, spatial repertoires, translanguaging, and translingualism, have also been widely discussed in writing studies, which corroborates the central principles of ' trans -' studies on writing. With this growing interest, ' trans -' principles have been increasingly enacted in writing practices, which has been reflected in the increasing use of the word combinations, such as translingual pedagogy, translanguaging pedagogy, and translanguaging space . The results also show that some terms, such as translingual writing, code-switching, code-meshing, and monolingualism, have been decreasingly discussed due to some misunderstandings of those terms and the relatively stable conceptualization of ' trans -' terms.